2002
DOI: 10.1002/ajmg.10679
|View full text |Cite
|
Sign up to set email alerts
|

De novo complete trisomy 5p: Clinical and neuroradiological findings

Abstract: Partial or complete duplication of 5p is a rare chromosomal abnormality in which genotype-phenotype correlation studies are hampered by other commonly associated chromosomal abnormalities. We report on a new patient in whom a complete de novo trisomy 5p in all metaphases represented the only chromosomal aberration. The present case further contributes to delineate the typical clinical picture of the trisomy 5p syndrome. Long-term clinical follow-up demonstrated low levels of secretory immunoglobulin A (IgA) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
2
12
3
Order By: Relevance
“…In both cases trisomy of 5p15.22 was confirmed. These findings support the observations made by Grosso et al [2002] and suggest a periventricular heterotopia locus along the telomeric end of chromosome 5p. In our patient the cerebral computed tomography scan showed atrophy of the frontal lobe, small subarachnoid space and a probable cortical dysplasia, but we were unable to do a brain magnetic resonance imaging.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In both cases trisomy of 5p15.22 was confirmed. These findings support the observations made by Grosso et al [2002] and suggest a periventricular heterotopia locus along the telomeric end of chromosome 5p. In our patient the cerebral computed tomography scan showed atrophy of the frontal lobe, small subarachnoid space and a probable cortical dysplasia, but we were unable to do a brain magnetic resonance imaging.…”
Section: Discussionsupporting
confidence: 90%
“…The differences in the phenotype between our patient and Kleczkowska et al could be explained by variability or by subtle differences in the involved segments. Grosso et al [2002] suggested that recurrent respiratory infections observed in patients with trisomy 5p might been explained by low secretory IgA levels; unfortunately this observation was not studied in our patient, although she did not have a history of recurrent respiratory infections. Grosso et al [2002] also suggested that the chromosome 5p may contain gene(s) playing a role in central nervous system development that may explain the cerebral dysgenesis observed in some patients with trisomy 5 [Kleczkowska et al, 1987;Zhao et al, 1995].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Tertiary trisomy including the der(5) following 3:1 segregation results in trisomy for the whole short arm of chromosome 5, which is associated with severe malformations and mental retardation. Over 40 cases with partial trisomy of 5p have been reported to date (Grosso et al 2002). The corresponding tertiary monosomy would result in a constellation with a cri-du-chat syndrome, a welldescribed partial monosomy resulting from deletion of the short arm of chromosome 5.…”
Section: S U M M a R Ymentioning
confidence: 99%
“…It can be partial or complete, resulting from different cytogenetic mechanisms such as duplications, insertions, isochromosomes, or complex rearrangements [Reichenbach et al, 1999;Velagaleti et al, 2000;Grosso et al, 2002;Cervera et al, 2005;de Carvalho et al, 2008;Loscalzo et al, 2008;Oexle et al, 2011]. Less than a dozen patients with sSMCs resulting in trisomy 5p have been described; however, a critical region between 5p10 and 5p13.1 was postulated comparing data from patients with partial 5p duplications [Lorda-Sánchez et al, 1997].…”
mentioning
confidence: 99%